Frühstück im Freien - Freiräume im offiziellen Kunstbetrieb der DDR. Die Ausstellungen und Aktionen im Leonhardi-Museum in Dresden 1963 - 1990 - Weißbach, Angelika (Q-Serie, 2009)
The Leonhardi-Museum in Dresden belonged to one of the most legendary exhibition centers / galleries for contemporary nonconformist art in the GDR. Its peculiarity was derived from the fact that the concept and organization of the exhibitions lay in the hands of the artists themselves - who continually formed open ad hoc working groups (Arbeitsgruppe / AG) - as well as the fact that it was not an unofficial or autonomous institution, but primarily a gallery belonging to the State Association of Artists in the Graphic Arts in the GDR (VBK) and later to the city council Dresden-East. This dissertation examines and documents more than 100 exhibitions and events held in the principal hall of the Leonhardi-Museum between 1963 and 1990. The majority were personal exhibitions by graphic artists, painters and sculptors which provoked attitudes and opinions, broadened viewing habits and which featured experiments which were stimulated by the dimensions of the room. Often it was the first opportunity at all for artists to exhibit. Especially the communal festivities and spectacular group exhibitions around the topics "doors" and "Alfresco Breakfast" made the Leonhardi-Museum famous both nationally and internationally. Ministry of "Staatssicherheit" bans contributed to the increased popularity of the Leonhardi-Museum. Comparisons with similar official exhibition venues in Berlin (Lothar Lang's Art-Cabinet, Gallery Arkade), Leipzig (Gallery on the Sachsenplatz, Herbstsalon), Karl-Marx-Stadt (Gallery Clara Mosch) and Dresden (Galleries Kunst der Zeit, Nord, Comenius and Mitte; Puschkinhaus, Lücke frequentor, Intermedia) demonstrate that the importance of the Leonhardi-Museum changed, but that for three decades it remained the only place in the GDR in which artists were able to use official structures for their art. In doing so they created scope for freedom for the graphic arts.